“Living for Myself and Others”: The Role of an Ostomy Self-Help Group in Thailand in Providing Psychosocial Support - Niphattra Haritavorn; Chanika Nimsun (Global Qualitative Nursing Research)
The Thai ostomate self-help group is an informal association of people living with ostomy who come together with the goal of improving their quality of life and living conditions. This study aims to qualitatively explore the experiences of individuals with colostomy and their participation in a self-help group in Thailand. In-depth interviews were conducted with 30 individuals living with a permanent ostomy who had undergone ostomy surgery for colorectal cancer. Through engaging with the group, participants found ways to live for themselves and others. Information and support were shared in the form of positive stories that empowered participants to live a more normal life and participate in everyday activities. Moreover, group members found a sense of meaning and appreciation in devoting themselves to helping other members. These results enhance the understanding of the benefits of self-help groups in Thailand, and in turn raise question about the provision of psychosocial services for people living with ostomy in the Thai health care system.